PENGARUH LITERASI KEUANGAN, PROMOSI PENJUALAN DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF PENGGUNA PAYLATER - Mellisa, Mellisa; Rosmida, Rosmida (Universitas YPPI Rembang, 2023)
The purpose of this study was to determine: (1) the effect of financial literacy on the consumptive behavior of paylater users. (2) the effect of sales promotion on the consumptive behavior of paylater users. (3) the influence of lifestyle on the consumptive behavior of paylater users. (4) the effect of financial literacy, sales promotion, and lifestyle on the consumptive behavior of paylater users. This research is a type of quantitative research using primary data sources (questionnaires). The sampling technique used purposive sampling with 71 respondents. Data collection using a questionnaire via google form and analyzed using Hypothesis Test (T Test) and (F Test). The results showed that: (1) there is an influence of financial literacy on the consumptive behavior of paylater users. (2) there is no effect of sales promotion on the consumptive behavior of paylater users. (3) there is an influence of lifestyle on the consumptive behavior of paylater users. (4) there is a simultaneous influence of financial literacy, sales promotion, and lifestyle on the consumptive behavior of paylater users.